Translators - Rot Gabrovec, Veronika (ELOPE (Ljubljana), 2015)
The article explores various representations of culture(s) found in contemporary English children's literature and discusses how they were rendered into Slovene. In the first part, some introductory definitions of culture and approaches to the translation of children's literature are presented. In the second part, excerpts from selected literary works (for instance, Mary Poppins, Harry Potter and the Philosopher's Stone, Matilda, The Curious Incident of the Dog in the NightTime) are examined, both from the source and the target texts, with more attention paid to the cultural contexts, and the social changes that possibly influenced the translator's decisions.
Keywords: children's literature; culture; družba; kultura; otroška književnost; prevajanje; society; translation